A well-connected Earth : The science and conservation of organismal movement - Jedediah F., Brodie; Andrew, Gonzalez; Mohd Azlan, Jayasilan; Cara R., Nelson; Gary, Tabor; Divya, Vasudev; Katherine A., Zeller; Robert J ., Fletcher Jr (American Association for the Advancement of Science, 2025)
Global biodiversity targets focus on landscape and seascape connectivity as a foundational component of biodiversity conservation, including networks of connected protected areas. Recent advances allow the measurement and prediction of organismal movements at multiple scales. We provide a definition of connectivity that links movement to persistence and ecological function. Connectivity science can guide planning for biodiversity, ecosystem services, ecological restoration, and climate adaptation. Ongoing climate change and land and sea use are closing the window of opportunity for connectivity conservation. A coordinated global effort is required to implement scientific knowledge and to monitor, map, protect, and restore areas that promote movement and maintain well-connected ecosystems for biodiversity in the long term.